Texel and Dohne Merino highlight preweaning growth in the high andean highlands of Peru: A comparative study of six sheep breeds - Arias Arredondo, Alberto Gilmer (2025)
Sheep production in the high Andean regions of Peru faces several challenges, including low productive performance, particularly during the pre-weaning stage. Therefore, the appropriate selection of breeds adapted to these conditions could significantly improve growth indicators and increase the profitability of the production system. The study aimed to compare the behavior of preweaning growth criteria in male and female lambs of six sheep breeds (Dohne Merino, Corriedale, Texel, Poll Dorset, Finnish Landrace, and East Friesian) raised in the high Andean conditions of Peru. A total of 199 live weight records of lambs were evaluated at birth, 25, 60, 90 days, and weaning. The analysis of variance revealed significant differences between breeds, separated by sex, and the Principal Component Analysis examined patterns of variation among variables and breeds. The results showed that males of the Texel breed had a higher average weight at 60 days, while the Dohne Merino breed stood out in terms of birth weight. In females, Texel and Dohne Merino were the breeds with the highest weights at 90 days and weaning. PCA analysis revealed a positive correlation between 60-day, 90-day, and weaning weights, although no clear grouping by breed or sex was evident. However, Texel and Dohne Merino showed better performance compared to the other breeds, suggesting their potential for inclusion in genetic improvement programs under high-altitude conditions, which could contribute to strengthening livestock systems in the high Andean regions of Peru.